A direct determination of the number of light neutrino families from e+ e- → vvγ at LEP - Dova, María Teresa (1992)
The L3 detector at LEP has been used to determine the number of light neutrino families by measuring the cross section of single photon even in e+e - collisions at energies near the Z° resonance. We have observed 61 single photon candidates with more than 1.5 GeV of deposited energy in the barrel electromagnetic calorimeter, for a total integrated luminosity of 3.0 pb-1. From a likelihood fit to the single photon cross sections, we determine Nv = 3.24 ± 0.46 (statistical) _+ 0.22 (systematic).